KEPUTUSAN PEMBELIAN PAKET UMRAH OLEH JAMA’AH PT. PENJURU WISATA NEGERI KOTA PEKANBARU - Lisa Putri Yati; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Purchasing decisions are individual activities that are directly involved in making decisions to make purchases of the products offered by the seller. In this study, the product for researching consumer is a tour package product from the umrah travel sector, specifically the umrah package. Tour packages are a combination of tourism components consisting of transportation, tourist attractions,food,and tour leader services that is sold to tourist in one price. This research aims to determine the process of purchasing an umrah package by umrah pilgrims at Andalas Education Tour. The Data collected using interview techniques, questionnaires, and documentation. Based on the research that the author has done, the company has been very good at providing facilities and services to umrah pilgrims, but the company still needs to increase promotion to raise awareness of prospective pilgrims about the brand and products of Andalas Education Tour. Key Word : Purchasing Decisions, Umrah Packages